COMPOSITE ACTIVATING COATING EFFECT ON WELD GEOMETRY - Vyacheslav A. Lenivkin; Dmitry V. Kiselev; Sergey G. Parshin (Advanced Engineering Research)
The effect of the composite activating coating based on the halide salts upon the weld geometry under gas-shielded welding by the reverse polarity current has been investigated. The dependence of the fusion penetration on the electrode wire coating is found out.